Open Repository Explorer and Visualizer (OpenRXV) - Al-Najdawi, Moayad; Al-Rowad, Mohammed; Orth, Alan S.; Mahmoud, Abdullah; Foqha, Abdullah; Rahahleh, Yosef (International Livestock Research Institute, 2021)
The Open Repository Explorer and Visualizer (OpenRXV) is a dashboard-like tool that was created to help people find and understand content in open access repositories like DSpace.